2012
DOI: 10.4067/s0717-95022012000200044
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Accumulation in Actinic Cheilitis with Different Degrees of Epithelial Dysplasia

Abstract: SUMMARY:The extracellular matrix (ECM) plays an important role in the regulation of biological events such as the development of cell migration, proliferation and differentiation. Chronic sun exposure causes changes present in the ECM of actinic cheilitis (AC), a premalignant lesion of the lower lip which helps to understand the carcinogenesis of the lip. This study aimed to investigate elastin, the main component of solar elastosis alternating current in an attempt to establish the relationship between this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Others authors studied 35 cases of AC and observed that 17, 13 and 5 patients showed light, moderate, and severe dysplasia, respectively [20]. In the present study, we observed that, when present, epithelial dysplasia ranged from light to severe; only 2 cases showed no histological changes, which are characteristic of atypia.…”
Section: Discussionsupporting
confidence: 62%
“…Others authors studied 35 cases of AC and observed that 17, 13 and 5 patients showed light, moderate, and severe dysplasia, respectively [20]. In the present study, we observed that, when present, epithelial dysplasia ranged from light to severe; only 2 cases showed no histological changes, which are characteristic of atypia.…”
Section: Discussionsupporting
confidence: 62%
“…[EBP]) components of elastic fibers. 1 Studies on human skin exposed to UV radiation show that not only the degradation of ECM macromolecules but also SE increases the risk of developing cancer. 23 Elastosis has been associated with a worse prognosis and invasiveness in several types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Actinic cheilitis (AC) is an asymptomatic chronic inflammatory disorder, that transforms potentially into lip squamous cell carcinoma (LSCC). 1,2 AC may present epithelial alterations, solar elastosis (SE), and varying degrees of inflammatory infiltration. 3 The SE areas are constituted by collagen degenerations formed by the incidence of solar UV radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we believe that ultraviolet radiation has a significant effect on tissue remodeling and fibrosis in FP, based on the hypothesis that fibrocytes altered by ultraviolet radiation are related to induce the synthesis and excessive deposition of elastic material. 22,41,42 Hence, fibroblasts involved in tissue remodeling in FP differ phenotypically from those involved in the development of OF, suggesting differences in matrix composition between these lesions. The stronger association between MC accumulation and elastin synthesis in FP-in contrast to OF in which MC accumulation was associated with the synthesis of collagen fibers- supports the hypothesis that MC influence the growth and expansion of OF and FP through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells were counted using the Image J program and the mean number of positive cells was calculated for each case. The expression of elastin was analyzed in up to 10 fields at 100x magnification, applying scores ranging from +3 to 0, adapted from Fukushima et al and Araújo et al 21,22 A score of +3 corresponds to a diffuse increase of elastic fibers with mass pattern; +2 signifies a diffuse increase of elastic fibers; +1 reflects partial increase with focal clusters of elastic fibers; while 0 denotes the same characteristics as observed in the control group. The thickness and fragmentation of elastic fibers were also described.…”
Section: Methodsmentioning
confidence: 99%